2013
DOI: 10.1097/hjh.0b013e32835eb2cf
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and long-term slow breathing exercise on muscle sympathetic nerve activity in untreated male patients with hypertension

Abstract: In essential hypertension, MSNA is reduced during acute SLOWB, but remains unaltered following long-term SLOWB. Long-term SLOWB reduces office, but not ambulatory BP and HR. SLOWB attenuates cardiovascular response to mental stress, but not physical stressors. These findings may be indicative of beneficial SLOWB effects on stress reduction in essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 47 publications
9
35
0
1
Order By: Relevance
“…In the healthy state, MSNA represents global sympathetic outflow to the skeletal muscle linked to BP regulation with strong feedback from the arterial baroreceptors (Wallin, ) and respiratory modulation (Habler, Janig, & Michaelis, ). The reduction in MSNA observed during slow breathing at either RF or RF + 1 was similar to that demonstrated in previous studies where slow breathing was of 10–15 min duration (Fonkoue et al, ; Harada et al, ; Hering et al, ; Oneda et al, ). Two prior studies in healthy subjects indicated no effect of slow breathing on MSNA but the duration of the breathing exercise was much shorter being 3 (Limberg et al, ) or 4 min (Raupach et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the healthy state, MSNA represents global sympathetic outflow to the skeletal muscle linked to BP regulation with strong feedback from the arterial baroreceptors (Wallin, ) and respiratory modulation (Habler, Janig, & Michaelis, ). The reduction in MSNA observed during slow breathing at either RF or RF + 1 was similar to that demonstrated in previous studies where slow breathing was of 10–15 min duration (Fonkoue et al, ; Harada et al, ; Hering et al, ; Oneda et al, ). Two prior studies in healthy subjects indicated no effect of slow breathing on MSNA but the duration of the breathing exercise was much shorter being 3 (Limberg et al, ) or 4 min (Raupach et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Slow breathing has long been recognized to exert beneficial effects in a range of disorders including those related to the cardiovascular system and those associated with anxiety. Breathing at a low pace (5–6 breaths per min) has been shown to acutely decrease blood pressure (BP) in patients with post‐traumatic stress disorder (Fonkoue et al, ), and in the longer term decrease BP in patients with hypertension (Hering et al, ). In patients with heart failure, slow breathing either performed acutely or chronically reduced the cardiovascular reactivity to mental stress and improved various aspects of health‐related quality of life (Lachowska, Bellwon, Morys, Gruchala, & Hering ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Device-guided breathing has been used to treat hypertension and heart failure with mixed results (Hering et al, 2013; Howorka et al, 2013; Landman et al, 2013; de Barros, da Silva et al, 2014; Harada et al, 2014; van Hateren et al, 2014). The mixed result sparked a debate on what constitutes device-guided breathing (Huang and Subak, 2014; Landman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Likely mechanisms contributing include elevated reflex afferent drive from both peripheral chemoreceptors 14,15 and kidney, 16,17 saltangiotensin II, [18][19][20][21] inflammation, [22][23][24] and respiration. 13,[25][26][27][28][29] Respiratory modulation of sympathetic activity or respiratory-sympathetic coupling has been observed in many sympathetic postganglionic outflows. 13,21,[28][29][30][31][32][33] Clinical studies have purported that by controlling breathing depth and rate (using RespeRate) blood pressure can be lowered 34 in patients with hypertension.…”
mentioning
confidence: 99%